Binamasur-10, the first drought tolerant lentil variety registered in Bangladesh (Research in Agriculture Livestock and Fisheries, 2019)
from International Centre for Agricultural Research in the Dry Areas (ICARDA) including some advanced lines from Bangladesh Institute of Nuclear Agriculture in 2006. During Preliminary Yield Trial, the genotype LG-208 produced 18.62% and 29.47% higher seed yield than the check variety BARI Masur-5 at Ishurdi and Magura respectively. Through advanced yield trials, regional yield trials, on-station and on-farm trials from 2010-11 to 2015-16, it was found that exotic germplasm LG-208 showed better performance than check (BARI Masur-5). Genotype LG-208 had significantly highest seed setting and harvest index under 20% polyethylene glycol (PEG) induced drought and considered as the drought tolerant which showed similar performance with field trials in drought-prone areas (Chapainawabganj and Rajshahi). Based on the superior performance of exotic germplasm LG-208 line, BINA has decided with the National Seed Board (NSB) of Bangladesh to register this line as a high yielding drought tolerant lentil variety, named as Binamasur-10 in 2016.Res. Agric., Livest. Fish.6(2): 253-262, August 2019